The Diagnostic and Prognostic Value of Biochemical Markers of Acute Lung Injury - Ye. V. Grigoryev; Yu. A. Churlyaev; D. L. Shukevich; L. E. Shukevich; A. S. Razumov (Общая реаниматология)
Lipid peroxidation products and antioxidative system components were studied in 56 patients with a systemic inflammatory response of various genesis. The arterial blood levels of prooxidants were found to be associated with a poor outcome. The findings that there is an inverse correlation between lipid peroxidation products and the respiratory index allow the diagnostic and prognostic value of blood free radical oxidation products to be determined as markers of acute lung lesion.systemic inflammatory response; acute lung lesion; lipid peroxidation; diagnostic and predictive markers